PENGEMBANGAN INSTRUMEN TES KETERAMPILAN SHOOTING PADA PEMAIN SEPAKBOLA USIA 16-20 TAHUN - Muhammad Taufik Aziz; Khoiril Anam (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
The goal of this project is to develop a talent test instrument for football shooting accuracy for soccer players between the ages of 16 and 20. Utilizing research and development techniques, this study was undertaken. 36 participants, 6 PS UNNES players, 18 PS POP players, and 16 PS Tunas Sakti Mandiri players, were used as subjects in this study. In this study, the validation was conducted out by soccer course instructors, a professional club coach from the Indonesian 3rd League, and three coaches from the research sample clubs who were registered at the PSSI Ascot in Semarang city. The validity test uses content validity. The football shooting accuracy test, according to experts, falls into the "very good" category, making it practical to use or valid. The test-retest methodology combined with product moment correlation analysis is used for the reliability test. With a dependability rating of 0.843 and a significance level of 0.000, the accuracy test device for footballs is deemed reliable. With the findings of the aforementioned study, it is possible to use the football shooting accuracy test instrument as a measuring device for accuracy shooting tests for football players.